Implementasi Node-RED pada Sistem Pemantauan Suhu dan Kelembapan Tanah dalam Pengelolaan Tanaman - Sari, Mey; Ramadhan, Rauf; Ridwan, A; Rahman, Abdul (MDP Student Conference, 2025)
Soil temperature and humidity monitoring technology plays an important role in improving the efficiency of crop management. This study develops an Internet of Things (IoT)-based monitoring system using WeMos ESP8266 integrated with DHT22 sensor and Soil Moisture Hygrometer. Data is sent in real-time via MQTT or HTTP protocol to the Node-RED platform, which provides interactive visualization. This system allows for accurate monitoring of soil conditions in the event of an imbalance in humidity or temperature. Test results show that the system is able to detect three categories of soil moisture: dry, moist and wet, and improve water use efficiency. With the combination of MQTT and Node-RED, this system is more reliable and easier to use than conventional methods. The use of this technology has the potential to be further developed with watering automation features.